(untitled) (International Journal of Food and Nutritional Sciences, 2020)
India has been a fully developed planned economy since 1951. In order to establish the manufacturing and industrial sector as the foundation of the Indian economy, the first several plans concentrated on expansion and strengthening it. Planning also focused on social development, employment creation, poverty reduction, and agriculture. etc. India faced its worst economic and currency crisis ever in 1991, but the country’s economy recovered effectively after implementing economic reforms and the LPG (liberalization, privatization, and globalization) strategy. The Indian economy was then disrupted and going through another chaotic period in 2008 as a result of the global financial crisis. This paper analysis Indian economy from 1991-2013.